Yield improvement and genotype by environment interaction of selected bambara groundnut genotypes developed through pureline selection and molecular approaches - Khan, Md Mahmudul Hasan (2022)
As a crop for the new millennium, Bambara groundnut (Vigna subterranea [L.] Verdc.) is considered as a "miracle lucrative" legume for Asia and Africa because of its drought resilience, excellent nutritional profiles, and significant versatile uses. Due to minute floral biology and cleistogamous reproductive system, its potential for improvement through hybridization breeding is limited. However, addressing genetic diversity and pure line selection, along with molecular breeding issues are the most imperative and viable methods for its improvement, as a newly introduced legume in Malaysia. The progress of this underexploited legume has been limited owing to a lack of extensive research, marginalization, inadequate knowledge, and readily available research funding, among other concerns. In this point of view, a comprehensive breeding program is carried out. The main objective of this research work was to assess morphological variation considering 14 qualitative and 27 quantitative traits as well as advancing the generation via pure-line selection, genomic DNA analysis using inter-simple sequence repeat (ISSR) markers, genotype by environment (GEI) effects on yield components, and yield stability assessment to discover the superior variety. The plant materials were sourced from the GenBank of the Institute of Tropical Agriculture and Food Security, Universiti Putra Malaysia (UPM), Serdang, Selangor. The field experiment adopted a randomized complete block design (RCBD) with three replications. The recorded data were subjected to analysis of variance, correlation, principal component analysis, clustering pattern, and heatmap analysis, as well as genetic parameters estimation. Analysis of variance revealed significant differences at p ≤ 0.05 or p ≤ 0.01 signifying a degree of variability present in evaluated traits for all generations of evaluation (S0 to S5). The result showed a downward trend in values of coefficient of variation for yield trait as 55.15%, 30.18%, 19.37%, 18.74%, and 17.53% for selfed generation of S0, S1, S2, S3, and S4, respectively indicating that pure line selection is effective for this legume improvement based on yield trait. Additionally, in all rounds of evaluated generation (S0-S4), yield component traits such as total number of pods, fresh pod weight (g), hundred seed weight (g), dry pod weight (g), dry seed weight (g), and harvest index (%) had a positive and highly significant correlation (0.75 ≤ r ≤ 1.00; p ≤ 0.01) with yield trait. Selection based on these traits for this legume improvement may lead to higher success due to their estimated high heritability and genetic gain values of Hb ≥ 60% and GA ≥ 20%, respectively. In terms of molecular characterization, a set of 32 ISSR markers on forty-four accessions from S4 selfed generation, revealed 97.64% polymorphism with an average calculated polymorphic information content (PIC) was 0.243, Nei’s genetic diversity (h = 0.248), and Shannon’s information index (I = 0.395), which indicate the presence of a low to moderate level of genetic variability among the accessions. UPMGA phylogenetic tree clustered the entire genotypes into 3 major clusters and 6 sub-clusters that were also proved by admixture (Bayesian model) analysis which assembled genotypes into 3 distinct genetic components (membership likelihood Q > 0.60) based on best ΔK = 3. Within the population, estimated variation was higher as 75% compared to among the population of 25% with gene flow of Nm = 0.9229 indicating that higher-level genetic variation exists within the population. The total variation of 26.51% was revealed by principal component analysis (PCA) based on ISSR data, where PC1 (13.92%) > PC2 (12.59%). The path-coefficient analysis explored that dry pod weight had the highest direct effect on yield trait. GGE biplot represents the variation of the first two principal components, PC1 (94.97%) and PC2 (3.11%) for yield trait. The source of variation namely, genotypes (22.40%), seasons (31.13%), and locations (14.02%) were found to be the most significant causes of yield heterogeneity for overall G + E + G × E variation. The GGE biplot and AMMI revealed that the three winning lines S5G1 (MaikP12-18), S5G3 (Maik P6-18), and S5G5 (JataP1-18) appear as superior lines and in addition, based on ideal genotype ranking, line MaikP12-18 (S5G1) was highly stable, with a high mean yield across the environments. Conclusively, these three superior lines namely, S5G1 (MaikP12-18), S5G3 (Maik P6-18), and S5G5 (JataP1-18) are highly recommended for further large-scale evaluation before release as newly developed varieties for commercial cultivation in Malaysia.